Fuzzy And Level Sets Based Design Approch Fof Brain Tumor Segmentation (International Journal of Engineering and Computer Science, 2015)
This paper present deals with the implemention of Image enhancement, Linear contrast stretching, filtered image and bias field correction also Estimated that image. Normally the  Brain can be viewed by the MRI scan or CT scan. MRI scanned image is used for the entire process. The MRI scan is more comfortable than any other scans for diagnosis. It will not affect the human body, because it doesn’t practice any radiation. Modified fuzzy C means (MFCM) and level sets segmentation based methodology is proposed In future method.It allows  with high accuracy and reproducibility comparable to segmentation that also reduces the time for analysis also detection of range and shape of tumor in brain MRI Image.